2000
DOI: 10.1029/2000gl011762
|View full text |Cite
|
Sign up to set email alerts
|

Increasing background ozone in surface air over the United States

Abstract: The long‐term trend of background O3 in surface air over the United States from 1980 to 1998 is examined using monthly probability distributions of daily maximum 8‐hour average O3 concentrations at a large ensemble of rural sites. Ozone concentrations have decreased at the high end of the probability distribution (reflecting emission controls) but have increased at the low end. The cross‐over takes place between the 30th and 50th percentiles in May–August and between the 60th and 90th percentiles during the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…While peak ozone concentrations have decreased in the eastern U.S. during the ozone season, some sites also show increases in ozone at the low end of the distribution [Lefohn et al, 2010;Cooper et al, 2012] that may be due to reduced titration by NO or to increases in baseline ozone [Lin et al, 2000;Cooper et al, 2012], which is the ozone observed at sites without the presence of recent local pollution influence [Dentener et al, 2010]. A modeling study by Fiore et al [2002] found increases in ozone between 1980 and 1995 at the lower half of the distribution due to increases in Asian emissions.…”
mentioning
confidence: 89%
“…While peak ozone concentrations have decreased in the eastern U.S. during the ozone season, some sites also show increases in ozone at the low end of the distribution [Lefohn et al, 2010;Cooper et al, 2012] that may be due to reduced titration by NO or to increases in baseline ozone [Lin et al, 2000;Cooper et al, 2012], which is the ozone observed at sites without the presence of recent local pollution influence [Dentener et al, 2010]. A modeling study by Fiore et al [2002] found increases in ozone between 1980 and 1995 at the lower half of the distribution due to increases in Asian emissions.…”
mentioning
confidence: 89%
“…The term "background" was used in modeling studies that estimated the atmospheric mixing ratio of a compound determined by natural sources only, while the term "baseline" was obtained from measurement records by removing data affected by local influences (Chan and Vet, 2010). Various methods have been utilized to diagnose baseline conditions, including using measurements at remote sites, analysis of the probability distribution of pollutants, correlations with reactive nitrogen oxides, or isentropic back-trajectories (e.g., Lin et al, 2000;Derwent et al, 2007;Wilson et al, 2012). Air masses with monthly to annual low percentile values of CO are commonly considered baseline air (e.g., Lin et al, 2000;Mao and Talbot, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The PRB is an important factor in the NAAQS-setting process, as it represents a baseline of risk not amenable to domestic regulation [U.S. EPA, 2006]. Model studies indicate that the PRB background has a large intercontinental anthropogenic component [Fiore et al, 2002a[Fiore et al, , 2003a and observations show that it has been rising over the past three decades [Lin et al, 2000;Jaffe et al, 2003].…”
Section: Introductionmentioning
confidence: 99%